1973
DOI: 10.1144/gsjgs.129.6.0585
|View full text |Cite|
|
Sign up to set email alerts
|

The pre-Silurian rocks of Clare Island, Co. Mayo, Ireland, and the age of the metamorphism of the Dalradian Ireland

Abstract: The Highland Boundary Fault is considered to extend from Stonehaven in Scotland to the major Leek fault of Clare Island in western Ireland. This conspicuous fault of the island has however been erroneously correlated with the Leannan fault of Donegal, a probable branch of the Great Glen Fault. South of the Leek fault Silurian sediments rest unconformably upon a metamorphic basement. This consists of amphi-bolite facies metasediments intruded by basic and ultrabasic rocks that have also undergone amphibolite fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

1985
1985
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 18 publications
0
36
2
Order By: Relevance
“…This is comparable with the sedimentary history of the Highland Border Complex in Scotland. Here the Margie sandstones of upper Ordovician to possibly Silurian age are quartzrich, continentally derived (Curry et al 1984) and contain blue quartz similar to the sandstones of the Clew Bay Complex (Phillips 1973). Robertson and Henderson (1984) concluded that the provenance of these Scottish sediments was a Dalradian-like quartzo-feldspathic region.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is comparable with the sedimentary history of the Highland Border Complex in Scotland. Here the Margie sandstones of upper Ordovician to possibly Silurian age are quartzrich, continentally derived (Curry et al 1984) and contain blue quartz similar to the sandstones of the Clew Bay Complex (Phillips 1973). Robertson and Henderson (1984) concluded that the provenance of these Scottish sediments was a Dalradian-like quartzo-feldspathic region.…”
Section: Discussionmentioning
confidence: 90%
“…The latter are termed the Killadangan Formation on the mainland and the Ballytoohy Formation on Clare Island. Although originally considered to be part of the Dalradian succession (Phillips 1973), the Clew Bay Complex has more recently been shown to contain both Ordovician and Silurian elements (Williams et of. 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The complex fold pattern shown by Phillips (1973) was not reproduced by me during mapping and is regarded an artifact of correlating different, but lithologically similar beds between the discontinuous outcrops and across faults of unknown throw. In particular, units that Phillips (1973) regarded as tectonic breccias and large zones of D1 boudins are seen by me as being mixtite beds similar to those seen in the Cambrian rocks of Howth (Van Lunsen and Max 1975) and in the Gwna Group in the Bedded Succession on Anglesey (Shackleton 1969;Barber and Max 1979). Some of the larger isolated exposures of coarse greywackes might have proven to be mixtite rafts if exposure had been better.…”
Section: C Clare Islandmentioning
confidence: 92%
“…The group includes the Ballytoohy Formation of Clare Island (Phillips 1973) and the Killadangan Formation (Graham et ul. 1985) of the South Clew Bay Imbricate Zone (Kelly and Max 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation